Pendidikan Kewarganegaraan sebagai Sarana Internalisasi Nilai Pancasila - Millaty Azka; Nuroh Nihayatuz Ziyan; Ranaditya Maulana; Artika Arleawati (Jurnal Pendidikan dan Kewarganegara Indonesia, 2025)
Civic Education (PKn) has a strategic role as the main means in internalizing the values of Pancasila to students. Through PKn, the process of forming the character and personality of citizens can be carried out systematically, sustainably, and contextually, based on the values of divinity, humanity, unity, democracy, and justice. The internalization of these values is not only through mastery of concepts, but also through habituation of attitudes and behaviors in daily life. An interactive, reflective, and social project-based approach to learning allows learners to actively develop moral awareness, social responsibility, and a sense of nationalism. PKn functions as a character education instrument that not only forms civic knowledge, but also builds a strong national identity and a tolerant spirit. In the context of globalization and the challenges of the digital era, civil society is an important foundation in equipping the young generation to be able to be critical, adaptive, and still uphold national values. Therefore, PKn is not just a formal subject, but a strategic vehicle in forming a generation with Pancasila character who is ready to contribute positively to the life of society, nation, and state. This research emphasizes the urgency of PKn revitalization as a transformative and contextual value education.